Rational design of the nanostructure features on superhydrophobic surfaces for enhanced dynamic water repellency - Shen, Yizhou (2020)
Biomimetic surfaces with various extents of liquid adhesion intensely appeal to many researchers due to their academic significance and potential industry applications. The present work aims to discuss the relationship between bouncing dynamics of impact droplets and static liquid adhesion driven by micro/-nanostructure features. Here, we fabricated three types of nanostructure (nanotube, nanomesh, and nanowire) superhydrophobic surfaces based on the TiO2 nanomaterials, and all of these resultant surfaces were endowed with the robust superhydrophobicity, and showed the low liquid adhesion with the sliding angles from 7.5° to 3°. Subsequently, the bouncing dynamics of impact droplets on these surfaces were evaluated and showed remarkable distinctions with different capacity to rebound off. This is explained in that the impact droplet has induced a higher capillary-induced adhesion force interaction as compared to the static droplet on the nanotube structure surface due to the existence of dynamic pressure during the moving process. The produced high capillary-induced adhesion force interaction finally caused the impact droplet to not bounce off the surface. On the contrary, the impact droplet can successfully bounce off the nanowire structure surface, which is mainly due to the almost no capillary adhesion force interaction induced by the open structure system on the superhydrophobic surface.